Stability Studies Of Fuzzy Logic Based Power System Stabilizer In Enhancing Dynamic Stability Of A Two Generators Tie-Line System - Mohammed Hussein Hasan, Hayfaa; Sulaiman , Marizan; Jubair Al-Hiealy, Mohammed Rasheed; Omar, Rosli; Mohd Aras, Mohd Shahrieel; Mohamad Nor, Ahmad Fateh (Asian Research Publishing Network (ARPN), 2017)
Electro-mechanical oscillations are created, in the machines of an interrelated power network, followed by a trouble or due to high power transfer through weak tie lines. These oscillations should be damped as quickly as possible to guarantee the reliable and stable operation of the network. This research presents the analysis of change of speed, change of angle position and tie - line power flow, fuzzy logic controller (FLC) two area symmetrical systems connected via tieline are measured to show via performance of these controllers using Simulink/MATLAB. Simulation results described by fuzzy logic based controller having dual inputs of rotor speed deviation and generator’s accelerating power there shown better solutions for damping the inter area (tie-line) oscillations.